Counseling on Food Safety and Utilization of White Turmeric for Snack Bars at UMKM Amelia Bakery - Dwiyati Pujimulyani; Ichlasia Ainul Fitri; Wisnu Adi Yulianto; Mutaqin Akbar; Audita Nuvriasari; Umul Aiman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Indonesia has various types of empon-empon plants, one of which is white turmeric (Curcuma Mangga Val). This type of white turmeric contains curcuminoids and polyphenols which are useful as antioxidants. Utilization of these empon-empon as a daily snack will be very beneficial for health. However, the production of packaged food requires an understanding of food safety. The purpose of this community service is to conduct food safety education and apply white turmeric in the processing of snack bars. Implementation of safety counseling activities and processing of snack bars added with white turmeric at UMKM Amelia Bakery on October 26 2022, attended by employees. Snack bars with the addition of white turmeric powder were tested for preference at the UMBY Sensory Laboratory. The test sample is a snack bar sample with the addition of 5 g of white turmeric powder; 7.5g; and 10 g. UMKM Amelia Bakery employees understand food safety and the most preferred product is a snack bar with the addition of 5 g of white turmeric powder.